The Potential Role of Marine Protein Hydrolyzates in Elevating Nutritive Values of Diets for Largemouth Bass, Micropterus salmoides - Dai, Min; Li, Songlin; Fu, Cefeng; Qiu, Hongjie; Chen, Naisong (Frontiers in Marine Science, 2020)
The study was conducted to explore the improvement function of marine protein hydrolysates on nutritive values of diets for largemouth bass. The diet with no inclusion of marine protein hydrolysate was considered as the control (NC), and other four diets were formulated with fish soluble (FS), squid paste (SqP), shrimp paste (ShP), or a mixture of FS, SqP and ShP (Mix). Triplicate tanks of fish were fed to apparent satiation twice daily for 81 days. Results showed that the growth performance was elevated due to the inclusion of marine protein hydrolysates along with significantly elevated feed intake and protein digestibility. Thereinto, the inclusion of FS and ShP significantly improved the growth performance compared to NC. The supplementation of marine protein hydrolysates elevated the protein content and lysozyme activity of serum, while significantly decreased the activity of liver alanine transaminase and aspartate transaminase. The gene expression analysis revealed that marine protein hydrolysates inclusion up-regulated the expression of insulin-like growth factor I with increased expression of TOR pathway related genes including protein kinase B (AKT) 1 and ribosomal protein S6. However, the expression of activating transcription factor 4 (ATF4) and regulated in development and DNA damage responses 1 (REDD1) involved in amino acids response (AAR) pathway was depressed with the addition of marine protein hydrolysates. The activation of TOR pathway and depression of AAR pathway at the transcriptional level maybe benefit for the growth of fish. In above, the marine protein hydrolysate, especially FS and ShP, possessed the function to elevate nutritive values of diets for largemouth bass.